2017
DOI: 10.1039/c7cs00182g
|View full text |Cite
|
Sign up to set email alerts
|

Cross-coupling of aromatic esters and amides

Abstract: Catalytic cross-coupling reactions of aromatic esters and amides have recently gained considerable attention from synthetic chemists as de novo and efficient synthetic methods to form C-C and C-heteroatom bonds. Esters and amides can be used as diversifiable groups in metal-catalyzed cross-coupling: in a decarbonylative manner, they can be utilized as leaving groups, whereas in a non-decarbonylative manner, they can form ketone derivatives. In this review, recent advances of this research topic are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
200
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(203 citation statements)
references
References 142 publications
2
200
0
1
Order By: Relevance
“…Transition‐metal‐catalyzed cross‐coupling reactions of acyl electrophiles with aryl nucleophiles represent a powerful and reliable synthetic strategy for the introduction of acyl fragments into aromatic rings to provide aromatic ketones, and a large variety of carboxylic acid derivatives are currently used as acyl electrophiles . Among these, acyl fluorides have recently gained much attention as valuable carbon‐based electrophiles in cross‐coupling reactions, especially in acyl coupling and decarbonylative coupling reactions .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition‐metal‐catalyzed cross‐coupling reactions of acyl electrophiles with aryl nucleophiles represent a powerful and reliable synthetic strategy for the introduction of acyl fragments into aromatic rings to provide aromatic ketones, and a large variety of carboxylic acid derivatives are currently used as acyl electrophiles . Among these, acyl fluorides have recently gained much attention as valuable carbon‐based electrophiles in cross‐coupling reactions, especially in acyl coupling and decarbonylative coupling reactions .…”
Section: Methodsmentioning
confidence: 99%
“…Among these, acyl fluorides have recently gained much attention as valuable carbon‐based electrophiles in cross‐coupling reactions, especially in acyl coupling and decarbonylative coupling reactions . Due to the moderate electrophilicity of acyl fluorides, they exhibit a good balance between stability and reactivity with respect to their compatibility under nucleophilic conditions, that is, they are more stable than the commonly employed acyl chlorides, yet more reactive than the corresponding esters and amides . In fact, acyl fluorides are isolable using column chromatography on silica gel and can be used without any special precautions against moisture.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies revealed that first row transition metals, such as nickel, are effective in harnessing less reactive electrophiles, resulting in the exploration of less toxic and more economic cross‐coupling partners. Due to their non‐toxic and environmental friendly nature, particular attention has been drawn to the use of carboxylic acid derivatives, such as esters and amides, which proved successful especially in decarbonylative processes . Although nickel catalyzed decarbonylative reactions have been explored extensively among various research groups, the glove‐box is often a must in order to enable the use of moisture‐ and air‐sensitive ligands and/or catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their non‐toxic and environmental friendly nature, particular attention has been drawn to the use of carboxylic acid derivatives, such as esters and amides, which proved successful especially in decarbonylative processes . Although nickel catalyzed decarbonylative reactions have been explored extensively among various research groups, the glove‐box is often a must in order to enable the use of moisture‐ and air‐sensitive ligands and/or catalysts. Most of the developed methodologies are taking advantage of the high reactivity of catalysts and ligands, such as Ni(cod) 2 /dcype, for inert bond activation, which requires manipulation in a glove‐box.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Fori nstance,o ur lab and others recently showed that phenyl esters can be used to make amides (Scheme 1), ketones,biaryls,and more with Pd and Ni catalysis. [5] Fori nstance,o ur lab and others recently showed that phenyl esters can be used to make amides (Scheme 1), ketones,biaryls,and more with Pd and Ni catalysis.…”
mentioning
confidence: 99%